Seeking a homelan d sojourn and ethnic identity in the ancestral narratives of Genesis - Kennedy, Elisabeth Robertson. (Biblical Interpretation Series, 2011)
Sojourn is a Leitwort in the ancestral narratives of Genesis, repeatedly accentuated as an important descriptor of the patriarchs' identity and experience. This study shows that despite its connotations of alienation, sojourn language in Genesis contributes to a strong communal identity for biblical Israel. An innovative application of Anthony D. Smith's theory of ethnic myth utilizes the categories of ethnoscape, election, and communal ethics as analytical tools in the investigation of the Genesis sojourn texts. Close exegetical treatment reveals sojourn to strengthen Israel's ethnic identity in ways that are varied and at times paradoxical. Its very complexity, however, makes it particularly useful as a resource for group identity at times when straightforward categories of territorial and social affiliation may fail.